Total Harmonic Distortion of Dodecagonal Space Vector Modulation - Babita Nanda (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
Space vector modulation technique is one of the best PWM technique which has been implemented to the Multilevel inverter circuit to get the purely sinusoidal cuurent .This is a important algorithm which is implemented in open wind induction motor.This type of I.M has great impact on Electric Drive system. SVM is nothing but the technique of switching algorithm .The Hexagonal space vector modulation has been implemented before , but elimination of higher order harmonics are not possible. Torque pulsation arises. Speed control of Induction motor was not smooth .so Dodecagonal (12) structure developed. A 12 side polygonal space vector structure is meant for eliminating (6n±1) harmonics in the phase current waveform throughout the modulating range. A high resolution of PWM technique is proposed involving multiple 12 sided polygonal (Dodecagonal) structure that can generate highly sinusoidal voltage at a reduced switching frequency. In this paper different values of frequencies have been taken for harmonic analysis. SVM method features a higher level of dc-bus voltage utilization compared to the conventional PWM.DOI: http://dx.doi.org/10.11591/ijpeds.v4i3.4279